Implementation of a Pet Care Management System - D.M.M.P Gunaratne; S.M.D.S Bandara; H.M.T.S Sooriyabandara; M.G.D.P.M.B Chandrarathna; D. I. De Silva; H.M.P.P.K.H Samarasekara (International Journal of Engineering and Management Research, 2022)
The meteoric rise of web applications has brought with it, a new layer of convenience and ease to nearly all walks of life and has been continuously enabling faster and more efficient alternatives to previously geriatric systems. Thus, the field of ‘pet care’, which has been stagnant in its accessibility is also currently seeing a new dawn of integration with modern technology. Now more than ever, pet owners are keenly aware of the amount of care that their pets require in order to be well looked after. However, being busy with day-to-day struggles, the common pet owner is in dire need of a convenient system to help manage their pets needs. As a country that has put relatively little emphasis on the field itself, the implementation of a functional and accessible pet care management web application would undoubtedly elevate the level of care that pets would receive, whilst also significantly increasing the ease of pet owners managing their beloved companions. This paper aims to detail the thought process behind the implementation of the application, the technology used, the services and functionalities provided, and the needs that both pet owners and pets alike would appreciate the app catering towards.